The Effect of Service Quality, Facilities and Promotion on The Interest of New Students - Umin Kango; Ari Kartiko; Bahruddin Zamawi (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2021)
In the world of education has a very rapid development, especially in private schools which will have an impact on these schools to gain the sympathy of prospective new students . The International Standard Madrasah (MBI), Amanatul Ummah, has improved academic services, infrastructure and promotion to attract the public to foster the interest of new students. This research was conducted at MBI Amanatul Ummah located in Pacet District, Mojokerto. This study examines the independent variables consisting of service quality, infrastructure and promotion variables, while the measured (bound) variable is the interest of new students. This study uses primary data sources obtained through questionnaires that have been filled in by respondents . To test the hypothesis of this study using multiple linear regression , showed that equation , Y = 7,580 + 0.3 7 8 + 0 442 + 0.1 5 8 . A constant (α) of 7,580 shows the amount of interest of new students , if there is no influence from the variable quality of service ( ), infrastructure ( ) and promotion ( ) or it can be said that if the independent variable is zero then the amount of interest of new students is according to the constant value , namely 7,580 . t-test results for playanan quality variables.